Development and evaluation of Salmonella Toxoid vaccine for poultry* - BHATTACHARYYA, D K; RAHMAN, H; MURUGKAR, H V (The Indian Journal of Animal Sciences, 2014)
A formalized Salmonella Toxoid vaccine against avian salmonellosis was developed from toxins ofa strain of Salonella Weltevreden (BM/1643) and was evaluated for the efficacy in respect of protection against homologous and heterologous challenges in poultry. The birds were vaccinated subcutaneously at 3rd and 5th week of age. The immunized birds was challenged intraperitoneal1y and orally with homologous (S. Weltevreden) and heterologous (S Typhimllrium and S Gallinarum) serovars at 4th week post-primary vaccination. The vaccine afforded 100% protection with S. Weltevreden and S. Typhimurium respectively. However, the cross protection was 83.33% with S Gallinarlim. The protective index of the vaccine was 94.00%. The challenged immunized birds shed less salmonellae than the non-immunized birds. The peak serum antibody titre was observed at 4th week post-primary vaccination, which declined gradually thereafter till the 9th week of observation.